Improving the Efficiency of the Vilnius City Transport System in the Context of Sustainable Mobility and Multimodality - Jarašūnienė, Aldona; Česnulaitis, Domas (The Baltic Journal of Road and Bridge Engineering, 2021)
Vilnius is one of the most dynamic cities in Eastern Europe experiencing a continuous increase in the number of vehicles and the development of road transport networks associated with a wide range of environmental impacts, greenhouse gas emissions, depletion of raw materials, energy and fuel consumption and also a social impact, expressed in the quality of life of people, human health, traffic jam and economic impact because of generated losses of economic efficiency. Different strategies have been adopted by the city of Vilnius to tackle the increasing traffic flows with a modest impact and without a long-term effect. This article aims at analysing the measures taken to improve the transport system of Vilnius city and presenting different types of solution, which could improve interconnectivity of passenger transport as ways to solve the problems of the urban transport system.